Public Green Space Availability in Semarapura Urban Area - Dewa Putu Aris Sadana; Nyoman Utari Vipriyanti; I Putu Sujana (The Indonesian Journal of Planning and Development, 2019)
Green Open Space (GOS), especially Public Green Space (PGS), plays an important role in implementing an urban area's sustainability. Until now, there has been no study of determining the PGS Availability in the Semarapura Urban Area. The study aims to determine PGS Availability in the Semarapura Urban Area based on the type, area, percentage, and area distribution of PGS. Data collection techniques in this study were field observations and secondary data surveys. The data analysis technique in this study is the Geographic Information System (GIS) or mapping. The results showed that Public Green Space (PGS) availability in Semarapura Urban Area was only 8.92 percent of Semarapura Urban Area's total area. This study's results can be used as a basis for determining the strategy of providing PGS in Semarapura Urban Area.